Correspondances de femmes et diplomatie (Espagne, France, Italie, IXe-XVe s.) - Lazzarini, Isabella; Nieto Soria, José Manuel; Rochwert-Zuili, Patricia (Studies, 2021)
This book collects the papers presented during the third colloquium of the MISSIVA research project, which took place on October the 28, 29 and 30, of 2019 at the École Française de Rome and the Istituto Storico Italiano per il Medioevo in Rome. The purpose of this meeting was to deepen the analysis of the political role of women in the Middle Ages through their correspondence to see if feminine diplomacy had existed and to determine, if necessary, its peculiarities. The studies proposed allow us to observe, over a long period -from the 9th to the 15th centuries- and in several geographical areas, a wide range of examples which testify to the sometimes decisive role of women's letters in the diplomatic game. As an instrument of mediation, negotiation and communication, women's correspondence highlights the different fields in which they intervene, according to their function and their social or family position, as well as the political and discursive strategies they implement.